2012
DOI: 10.1002/wdev.39
|View full text |Cite
|
Sign up to set email alerts
|

Annual fish: developmental adaptations for an extreme environment

Abstract: Annual fish are freshwater teleosts found in South America and Africa that are exposed to an extremely variable environment. They develop and reproduce in seasonal ponds that dry during the summer eliminating the entire adult population. Remarkably, desiccation-resistant embryos survive in these dry ponds that hatch during the next rainy season when the ponds are recreated. Among vertebrates, they represent one of the most remarkable extremophiles. They share several features with other fish models; however, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…In fact, others have suggested that the D/R process is simply an extensive prolongation of a normally very short part of teleost development (Berois et al, 2012). If this is the case, the data presented here are consistent with reduced IGF signaling playing a key role in this unique aspect of annual killifish development as well.…”
Section: Igf Signaling As a Potential Link Between D/r And Diapausesupporting
confidence: 87%
“…In fact, others have suggested that the D/R process is simply an extensive prolongation of a normally very short part of teleost development (Berois et al, 2012). If this is the case, the data presented here are consistent with reduced IGF signaling playing a key role in this unique aspect of annual killifish development as well.…”
Section: Igf Signaling As a Potential Link Between D/r And Diapausesupporting
confidence: 87%
“…Consequently, these fish are subject to extreme changes in physical and chemical characteristics over a short period (Volcan et al, 2011). Owing to their life cycle and peculiar adaptations to survive in the ephemeral habitats, annual fishes are considered extreme organisms (Berois et al, 2012(Berois et al, , 2014. The temporary wetlands in which they live are considered among the most threatened habitats worldwide (Amezaga et al, 2002) which compromises the conservation status of the organisms that depend on them (Gibbs, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The female has a predominantly light grey body, and a pale belly with several black spots (Figure 1b). Sexual dimorphism is an important characteristic in annual fishes, which suggests that sexual selection may play a key role in the differentiation, isolation, speciation and evolution of this group of fish (Berois et al, 2012).…”
Section: Resultsmentioning
confidence: 99%